Cellular prion protein protects from inflammatory and neuropathic pain - Zamponi Gerald W; Gadotti Vinicius M (SAGE Publishing, 2011)
Abstract Cellular prion protein (PrPC) inhibits N-Methyl-D-Aspartate (NMDA) receptors. Since NMDA receptors play an important role in the transmission of pain signals in the dorsal horn of spinal cord, we thus wanted to determine if PrPC null mice show a reduced threshold for various pain behaviours. We compared nociceptive thresholds between wild type and PrPC null mice in models of inflammatory and neuropathic pain, in the presence and the absence of a NMDA receptor antagonist. 2-3 months old male PrPC null mice exhibited an MK-801 sensitive decrease in the paw withdrawal threshold in response both mechanical and thermal stimuli. PrPC null mice also exhibited significantly longer licking/biting time during both the first and second phases of formalin-induced inflammation of the paw, which was again prevented by treatment of the mice with MK-801, and responded more strongly to glutamate injection into the paw. Compared to wild type animals, PrPC null mice also exhibited a significantly greater nociceptive response (licking/biting) after intrathecal injection of NMDA. Sciatic nerve ligation resulted in MK-801 sensitive neuropathic pain in wild-type mice, but did not further augment the basal increase in pain behaviour observed in the null mice, suggesting that mice lacking PrPC may already be in a state of tonic central sensitization. Altogether, our data indicate that PrPC exerts a critical role in modulating nociceptive transmission at the spinal cord level, and fit with the concept of NMDA receptor hyperfunction in the absence of PrPC.